2017
DOI: 10.1007/s11427-016-0387-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of apparent diffusion coefficient values in characterization of solid focal liver lesions: a prospective and comparative clinical study

Abstract: We evaluated and compared the diagnostic accuracy (DA) of apparent diffusion coefficient (ADC) values with that of lesion-to-liver ADC ratios in the characterization of solid focal liver lesions (FLLs). This prospective study was approved by the Institutional Human Ethics Board, after waiving written informed consent. Diffusion-weighted imaging and other routine magnetic resonance imaging were performed on 142 consecutive patients with suspected liver disease. The mean ADC values and lesion-to-liver ADC ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
9
1
1
Order By: Relevance
“…The results of this study showed that utilizing the monoexponential DWI, the ADC value of benign hepatic lesions was significantly higher than that of normal hepatic parenchyma ( Table 3, P < .001), which is consistent with the results of previous studies. [12][13][14][15][16][17] However, the results of this study also showed that the ADC values of malignant hepatic lesions and normal hepatic parenchyma were not statistically significant ( Table 3, P = .522), which is inconsistent with the results of previous studies. This may be related to the different malignant lesions included in this study, including primary and metastatic disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study showed that utilizing the monoexponential DWI, the ADC value of benign hepatic lesions was significantly higher than that of normal hepatic parenchyma ( Table 3, P < .001), which is consistent with the results of previous studies. [12][13][14][15][16][17] However, the results of this study also showed that the ADC values of malignant hepatic lesions and normal hepatic parenchyma were not statistically significant ( Table 3, P = .522), which is inconsistent with the results of previous studies. This may be related to the different malignant lesions included in this study, including primary and metastatic disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Students felt that learning genomics helped prepare them for future academic study [37] and created a more positive learning experience [40]. Thus, these publications indicate that incorporation of genomic education can be beneficial for high school student learning [38,39,44].…”
Section: High School Educationmentioning
confidence: 95%
“…Genomic education in high school is also important because high school biology is frequently not only the initial, but also the final formal exposure to genomics for many Americans [33]. Many high school students have the interest, maturity, and intelligence to learn and understand genomics, yet few studies involving high school students and genomic education have been conducted in the past five years (Table 1) [34][35][36][37][38][39][40][41][42][43][44]. Each of these studies incorporated teaching genomic principles to high school students.…”
Section: High School Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, nitric oxide may be a potential mediator of hepatic inflammation and fibrogenesis in AIH. The serum nitric oxide metabolites like inducible nitric oxide synthase (iNOS) and nitric oxide activity can reflect oxidant stress in the liver and detect the inflammation and disease progression (Lloyd, Phillips, Cooper, & Dunbar, 2008;Yang, Zhang, Han, Jin, & Yang, 2017). In addition, various surface markers and cytokines are expressed and secreted, respectively, by the classical activation (M1) and the alternative activation phenotypes (M2), both of which have variable impacts in the context of immunoregulation (Ivashkiv, 2013;Ka, Daumas, Textoris, & Mege, 2014;Ying, Cheruku, Bazer, Safe, & Zhou, 2013).…”
Section: Introductionmentioning
confidence: 99%